Design and optimization of a compact quasi-isochronous 180-deg transport arc with suppressed CSR-induced emittance growth - Zhang, Chengyi; Jiao, Yi (Frontiers in Physics, 2023)
Preserving the beam quality of a high-brightness electron beam from the source is a noteworthy issue when delivering the electron beam through a beam transfer line. In a beam transfer line with large deflection angle, e.g., a turnaround arc comprised of a series of dipoles, emission of coherent synchrotron radiation (CSR) can lead to transverse emittance dilution. Besides, the longitudinal dispersion may cause undesirable bunch length variation. Both effects can degrade the beam quality. In this study, design and optimization of a compact 180 deg transport arc comprised of muti-triple-bend achromat (TBA) cells are presented, aiming at suppressing the CSR-induced emittance growth and avoiding bunch length variation simultaneously. The TBA cells and the optics along the arc are adjusted to suppress the CSR-induced emittance growth and bunch length variation cell by cell, after which a global optimization of the arc is conducted. Practical considerations including nonlinear particle dynamics and a full 1-dimensional CSR model (including transient CSR at dipole edges and CSR in drifts) are taken into account.